Gastrointestinal Helminth Parasites in Freshwater Fish from Kuching, Sarawak - Zahari, A.Z; Intai, B; Shalene, H.; Tuloi, R. (Faculty of Medicine and Human Sciences, 2011)
Helminthic infection can cause diseases in both man and domestic animals, especially in developing countries. The incidence of parasitic diseases in fish is very common. In particularly, of all the known species of helminthes, 30 000 species (including the socio-economic importance) are known from marina and freshwater fishes. However there are no significant studies conducted on helminthic infection in freshwater fish, apart from the other studies done on water creatures such as snail and crab. Since there are minimal studies being conducted on freshwater fish, our group conducted an investigation for the presence of parasites, particularly helminthic parasite in the gastrointestinal tract of freshwater fish. A total of 12 specimens of catfish were randomly selected from a wet market in Kuching, Sarawak from October to December 2010. All the specimens were subjected to examination for gastrointestinal helminthes parasites during that period. The weight and length of the fish were measured prior to dissection. The morphological examinations of the parasites were done under the light microscope. Five out of 12 samples (42%) were found to be positive with gastrointestinal helminthes infection. The dominant parasites found had a higher chance to be from the phylum Nematoda (5 out of 8 samples) and followed by Trematoda (3 out of 8 samples). Out of 4 fertilised female fishes, 3 were found positive with helminthes parasites. Five out of 8 samples (62.5%) were found in the intestine of the fish and 3 (37.5%) were found in the stomach. Our finding indicates that fishes that were breaded in a closed-area or in ponds have higher chances to have a helminthic infection of the gastrointestinal tract compare to opened-area.